ANALISIS STRUKTUR EKONOMI DAN SPESIALISASI SEKTOR EKONOMI DI DAERAH SUMATERA UTARA TAHUN 2017-2021 - Togi Marito Simanjuntak; Angelicha Christina; Deris Dermawan (FEB Universitas Maritim Semarang, 2022)
Abstract. National economic development and regional economic development are two very closely related matters. This study aims to analyze the economic structure and specialization of the economic sector so that it can determine the main sectors, groups that are classified as advanced and sectors that are classified as slow and analyze the competitiveness of each sector in North Sumatra Province. This study uses the Shift Share analysis method. The data used in this study is secondary data in the 2017-2021 interval. The data used is secondary data, namely data obtained from records, books and journals in the form of financial reports for company publications, government reports, articles, books such as theories, journals, etc. The results of this study are expected to be an academic foundation for development in the North Sumatra area.